National Youth Survey (United States): Wave III, 1978 - Elliott, Delbert S. ([Verlag nicht ermittelbar], 1986)
Youth data for the third wave of the National Youth Survey are contained in this data collection, which includes data for youth interviewed in 1979 about events and behavior of the preceding year. The first wave of this study was conducted in 1976 (ICPSR 8375) and the second wave in 1977 (ICPSR 8424). Data were collected on the demographic and socioeconomic status of respondents, disruptive events in the home, youth aspirations, expectations for future goals, social isolation, normlessness, labeling, perceived disapproval, attitudes toward deviance, exposure and commitment to delinquent peers, sex roles, attitudes toward sexual assault, interpersonal violence, pressure for substance abuse by peers, exposure to substance abuse by parents, self-reported delinquency, and drug and alcohol use.